Theory of Planned Behavior’s Method on Knowledge and Preventive Behavior Toward Tuberculosis - Uly Agustine; Shelfi Dwi Retnani Putri Santoso; Sri Mugianti; Suprajitno Suprajitno; Wanto Paju; Hamid Hamid; Otik Widyastutik (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Tuberculosis (TB) is an infectious disease that has become a global health concern, with Indonesia being the country with the second-highest number of pulmonary TB cases after India. The level of knowledge and preventive behavior regarding TB significantly influences both the spread and the success of TB treatment. This study aims to evaluate the impact of health education based on the Theory of Planned Behavior (TPB) on TB prevention knowledge and behavior among patients. The study design utilized a quasi-experimental approach with control and intervention groups, where the intervention was administered through face-to-face education and followed by smart chat support sessions for one month. A total of 50 respondents participated, divided into treatment and control groups. Data analysis employed the Wilcoxon Signed Ranks Test and Mann-Whitney tests. The study results show that the statistical analysis indicated a significant improvement in knowledge and preventive behavior in the intervention group post-intervention (p=0.000), while the control group showed no significant change. The finding of this this improvement suggests that TPB-based interventions, which encompass attitudes, subjective norms, and perceived behavioral control, are effective in influencing health behavior changes. The conclusion is TPB-based health education through face-to-face sessions and smart chat follow-ups can be recommended as an intervention strategy to enhance TB prevention knowledge and behavior among high-risk populations.